Haier: A Hammer Turned a Company into Billion Dollar - Durrani, Bilal; Saeed, Muhammad Kamran; Mahmood, Kashif (Advances in Social Sciences Research Journal, 2022)
This case study examines the key strategic roles of Haier Pakistan management in overcoming the Chinese products image in Pakistani consumers. The case revolves around a MNC company which entered in Pakistan and faced the issue of bad word of mouth regarding Chinese Brand/Products. The benefits of case study is it will help the reader to better understand what needs to be done in marketing a product, what strategies should be used to overcome a bad word of mouth and make the company grow.